DAMPAK GAGAL BAYAR (DEFAULT) SUKUK IJARAH PT BERLIAN LAJU TANKER TERHADAP INVESTOR DAN PASAR KEUANGAN SYARIAH - Salsabila Putri Tsarwah; Baidhowi Baidhowi (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
Sukuk Ijarah is a certificate that contains the name of the owner and symbolizes ownership of assets that aim to be leased, or ownership of benefits, and or ownership of services according to the number of securities purchased in the hope of getting profit from the rental proceeds that are successfully realized based on ijarah transactions. In addition to Islamic bonds being able to benefit, Islamic bonds can also pose a risk, one of which is the risk of default. PT Berlian Laju Tanker, Tbk (BLTA) is one of them, this incident certainly has a significant impact on investors and the credibility of the Islamic financial market in Indonesia. Therefore, this article discusses the impact of PT Berlian Laju Tanker's sukuk ijarah default on investors and Islamic financial markets. The method used in this research is a descriptive qualitative approach, using secondary data from journals and sources. The results showed that this default was caused by the application of a fixed interest system in the ijarah reward scheme which is contrary to the principle of profit sharing in Islamic finance as well as the use of sukuk funds to pay old debts, not for productive activities. The impact of this incident includes financial losses for investors, decreased trust in sukuk, and reduced liquidity in the Islamic financial market. In addition, this case has encouraged regulators such as the Financial Services Authority (OJK) and the National Sharia Council of the Indonesian Ulema Council (DSN-MUI) to tighten regulations to improve transparency and investor protection in sukuk issuance